2021
DOI: 10.1097/md.0000000000024802
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of TCF3-PBX1 gene fusion, and chromosomal aberration in a pediatric pre-B cell acute lymphoblastic leukemia with clitoris swelling

Abstract: Rationale: Clitoris swelling as the initial clinical presentation of acute lymphoblastic leukemia (ALL) is extremely rare. These patients may be misdiagnosed with acute myeloid leukemia or solid tumor, and the main treatment can also be delayed. Patient concerns: A 2.10-year-old girl was referred to the pediatric surgery clinic with a worsening onset of clitoris swellings. The patient was afebrile and well appearing. Multiple retroperitoneal mass were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…CD9, CD123, and TdT were used to predict TCF3-PBX1. According to previous studies, most leukemic cells with TCF3-PBX1 have a characteristic immunophenotype of homogeneous CD19, CD10, and CD9 expression and a total lack of CD34 [7]. The value of CD9 was confirmed and approved by this study since this group showed the highest expression of CD9.…”
Section: Discussionsupporting
confidence: 74%
“…CD9, CD123, and TdT were used to predict TCF3-PBX1. According to previous studies, most leukemic cells with TCF3-PBX1 have a characteristic immunophenotype of homogeneous CD19, CD10, and CD9 expression and a total lack of CD34 [7]. The value of CD9 was confirmed and approved by this study since this group showed the highest expression of CD9.…”
Section: Discussionsupporting
confidence: 74%